2021
DOI: 10.1186/s12913-021-06058-3
|View full text |Cite
|
Sign up to set email alerts
|

On the move: exploring Inuit and non-Inuit health service providers’ perspectives about youth, family and community participation in care in Nunavik

Abstract: Background Literature about participation in health and social services suggests that youth, and more specifically Indigenous youth, are difficult to engage within health and social services. Youth are less likely to access services or to actively participate in decision-making regarding their personal care. Service providers play a crucial role in engaging youth based on the ways in which they seek, establish, and maintain relationships with youth and their families. The way in which providers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Their high turnover rates also prevent most non-Inuit staff from acquiring experiential knowledge of local socio-cultural realities. Difficulties of collaborating between services, amongst professionals, and between Inuit and non-Inuit workers have also been highlighted [ 50 , 54 ]. In a previous study, many non-Inuit workers indicated not knowing what other resources were available within the community, while Inuit felt that in order to develop trusting relationships and good collaboration, it was fundamental that non-Inuit be integrated in the community and learn from Inuit [ 50 ].…”
Section: The Atautsikut Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…Their high turnover rates also prevent most non-Inuit staff from acquiring experiential knowledge of local socio-cultural realities. Difficulties of collaborating between services, amongst professionals, and between Inuit and non-Inuit workers have also been highlighted [ 50 , 54 ]. In a previous study, many non-Inuit workers indicated not knowing what other resources were available within the community, while Inuit felt that in order to develop trusting relationships and good collaboration, it was fundamental that non-Inuit be integrated in the community and learn from Inuit [ 50 ].…”
Section: The Atautsikut Projectmentioning
confidence: 99%
“…Difficulties of collaborating between services, amongst professionals, and between Inuit and non-Inuit workers have also been highlighted [ 50 , 54 ]. In a previous study, many non-Inuit workers indicated not knowing what other resources were available within the community, while Inuit felt that in order to develop trusting relationships and good collaboration, it was fundamental that non-Inuit be integrated in the community and learn from Inuit [ 50 ]. Inuit and non-Inuit have indeed expressed numerous times the desire and need to better work together and share knowledge, with the aim to improve services for youth and families [ 54 ].…”
Section: The Atautsikut Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Inuit families talk about their fear of seeking help, fear of being judged or misunderstood by workers regarding their educational methods and fear that their child will be taken into the care of child welfare [ 15 ]. Families may try to use the services but may terminate their follow-up early which can at times lead to the imposition of services through court orders [ 16 ]. Non-Inuit workers sometimes understand these abrupt terminations as Inuit being resistant to the help offered, or as Inuit `culture` not being prevention-oriented [ 16 ].…”
Section: Main Textmentioning
confidence: 99%
“…Families may try to use the services but may terminate their follow-up early which can at times lead to the imposition of services through court orders [ 16 ]. Non-Inuit workers sometimes understand these abrupt terminations as Inuit being resistant to the help offered, or as Inuit `culture` not being prevention-oriented [ 16 ].…”
Section: Main Textmentioning
confidence: 99%